Network Pharmacology and In Vivo Analysis of Dahuang-Huangqi Decoction Effectiveness in Alleviating Renal Interstitial Fibrosis. (25th May 2022) - Luo, Yan; Xuan, Chen; Cheng, Junxiong; Xiong, Yu; Cao, Wenfu
Abstract : Dahuang and Huangqi are the most frequently prescribed treatment methods for chronic kidney disease in China. Our study aimed to clarify the pharmacological mechanism of action of Dahuang-Huangqi decoction (DHHQD) in renal interstitial fibrosis (RIF). The intersection of genes targeted by DHHQD active ingredients and RIF target genes was searched using network pharmacology to build a chemical ingredient and disease target network. For in vivo analysis, Sprague–Dawley rats with unilateral urethral obstruction (UUO) were administered DHHQD, and their kidney function-related indicators and pathological indices were determined. The expression of core targets was quantified using real-time polymerase chain reaction and western blotting. A total of 139 common targets for DHHQD and RIF in chronic kidney disease were detected. Compared with the untreated UUO rats, the DHHQD-treated rats showed reductions in the following: blood urea nitrogen and serum creatinine levels, kidney tubular atrophy and necrosis, interstitial fibrosis, hyperplasia and abnormal deposition of extracellular matrix, and microstructural changes in the mesangial matrix and glomerular basement membrane. DHHQD treatment significantly regulated the levels of renal core proteins, such as eNOS, IL-6, EGFR, and VEGF and reduced the mRNA and protein expression of the core targets involved in inflammation pathways, such as PI3K/AKT and TLR4/NF- κ B. DHHQD treatment ameliorated the severity of RIF by potentially regulating the AKT/PI3K and TLR4/NF- κ B signaling pathways. Our study findings provide insights into the mechanisms associated with DHHQD action and essential data for future research.